The impact of the use of mathematical representations in academic achievement and retention of learning Math with an average first-grade students (Journal of the College of Basic Education, 2022)
The technical sophistication of Modern technical development dictates the development of educational systems, which calls for a reorganization of educational content and teaching methods that depend on the participation of the learner instead of methods that depend on his reception of information. Therefore, the problem of the study arose with the following question: Does the achievement of mathematics and retention of learning differ among first-grade intermediate students? When they were taught mathematics according to inverted learning compared to the traditional method, where the research sample consisted of (78) students, and by (39) for each group was divided into two groups, an experimental group that studied according to inverted learning and a control group that studied according to the usual method. An equivalence was conducted for the sample in the variables (chronological age, previous achievement in mathematics, educational level of the parents). The researcher prepared an academic achievement test in mathematics (multiple choice) that consisted of (23) items, and its apparent validity and content validity were verified, and its reliability coefficient was (0.85) using Cronbach's alpha equation.The experiment was applied in the second semester of the academic year 202021, and after the completion of the experiment, the test was applied to the two research groups. After data collection and statistical analysis, the result was superiority of the experimental group over the control group in the achievement test and retention of learning, and in light of the results that were reached, the researcher developed her conclusions, recommendations and suggestions..